Contribution of Islamic Boarding School Education in Forming Students into a Multicultural Society - Januar, Januar; Hussin, Md Noor Bin; Hadini, Hadini (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2023)
This research aims to find out about the role of Islamic boarding schools in Islamic education, the multicultural education approach at the Baituridwan Islamic boarding school, multicultural education, and the integration of religious tolerance, as well as contributions to the formation of a tolerant Islamic society. The research method used in this study is a qualitative approach. Data collection techniques include in-depth interviews, document content analysis, and the use of questionnaires. The results of this research show that the role of Islamic boarding schools in Islamic education, namely providing formal education in Islamic religious studies, also promotes values such as noble morals, discipline, and devotion to religion. The multicultural education approach at the Baituridwan Islamic boarding school is based on the principle of respect for cultural diversity and provides a deep understanding of the values of multiculturalism, teaching them to respect the religions that exist in society. Multicultural education and the integration of religious tolerance, namely encouraging students to respect cultural and religious differences, they are taught to respect the practices and beliefs of other religions. The contribution to the formation of a tolerant Islamic society is creating a deep understanding of the values of pluralism and tolerance, overcoming prejudice and stereotypes towards other religions.